Fabricating TiO2 nanocolloids by electric spark discharge method at normal temperature and pressure. (23rd October 2017) - Tseng, Kuo-Hsiung; Chang, Chaur-Yang; Chung, Meng-Yun; Cheng, Ting-Shou
Abstract: In this study, TiO2 nanocolloids were successfully fabricated in deionized water without using suspending agents through using the electric spark discharge method at room temperature and under normal atmospheric pressure. This method was exceptional because it did not create nanoparticle dispersion and the produced colloids contained no derivatives. The proposed method requires only traditional electrical discharge machines (EDMs), self-made magnetic stirrers, and Ti wires (purity, 99.99%). The EDM pulse on time ( T on ) and pulse off time ( T off ) were respectively set at 50 and 100 μ s, 100 and 100 μ s, 150 and 100 μ s, and 200 and 100 μ s to produce four types of TiO2 nanocolloids. Zetasizer analysis of the nanocolloids showed that a decrease in T on increased the suspension stability, but there were no significant correlations between T on and particle size. Colloids produced from the four production configurations showed a minimum particle size between 29.39 and 52.85 nm and a zeta-potential between −51.2 and −46.8 mV, confirming that the method introduced in this study can be used to produce TiO2 nanocolloids with excellent suspension stability. Scanning electron microscopy with energy dispersive spectroscopy also indicated that the TiO2 colloids did not contain elements other than Ti and oxygen.